2019
DOI: 10.3390/ma12060877
|View full text |Cite
|
Sign up to set email alerts
|

Metal Oxide Thin Films Prepared by Magnetron Sputtering Technology for Volatile Organic Compound Detection in the Microwave Frequency Range

Abstract: Metal oxide thin films such as copper oxide, titanium dioxide, and tin dioxide deposited by magnetron sputtering technology were verified as a gas-sensitive layer in microwave-based gas sensors operated at 2.4 GHz. The developed gas sensors were tested at room temperature (23 °C) and 50% relative humidity (RH) under exposure to 0–200 ppm of selected volatile organic compounds (acetone, ethanol, and methanol) that are of high interest in industry and biomedical applications. The highest responses to acetone wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 61 publications
(39 reference statements)
1
26
0
Order By: Relevance
“…In this paper, a microwave gas sensor based on the tin dioxide (SnO 2 ) gas layer with UV illumination is investigated for acetone detection in the 0–200 ppm range at room temperature. The gas-sensing properties of SnO 2 at microwave frequencies were previously confirmed and presented in [30]. The obtained results strongly confirm that the UV illumination increases the developed sensor’s sensitivity for acetone, allowing for the detection of lower gas concentrations.…”
Section: Introductionsupporting
confidence: 74%
See 2 more Smart Citations
“…In this paper, a microwave gas sensor based on the tin dioxide (SnO 2 ) gas layer with UV illumination is investigated for acetone detection in the 0–200 ppm range at room temperature. The gas-sensing properties of SnO 2 at microwave frequencies were previously confirmed and presented in [30]. The obtained results strongly confirm that the UV illumination increases the developed sensor’s sensitivity for acetone, allowing for the detection of lower gas concentrations.…”
Section: Introductionsupporting
confidence: 74%
“…In the last few years, a number of papers have focused on enhanced acetone detection, utilizing various methods, such as optical detection [8,9,10], electrochemical sensors [11,12,13], metal oxides (MOXs)-based sensors [14,15,16,17,18,19,20], and analytical systems [21,22,23,24,25]. Microwave-based gas sensors with various gas-sensitive layers, including organic layers [26,27] and various MOXs layers [28,29,30], were investigated by the authors as well. The recently obtained results have shown that microwave gas sensors based on metal oxides can easily be utilized for acetone detection in the ppm range at room temperature [28,29,30].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The gas-sensitive layer can be realized based on various materials, including organic compounds (e.g., phthalocyanines [2,3]) and metal oxides [4] (e.g., WO 3 [5,6], TiO 2 [7,8], SnO 2 [9,10], In 2 O 3 [11,12], Fe 2 O 3 [13,14], MoO 3 [13,15], ZnO [16][17][18], CuO [19][20][21][22][23][24][25][26][27][28]). The most common methods for metal oxide depositions are magnetron sputtering [29,30], sol-gel [31,32], thermal oxidation [33,34], hydrothermal techniques [35,36], the spray pyrolysis technique [37,38], and the microwave-assisted method [39,40]. Among them, magnetron sputtering is widely accepted for industrial purposes, because it can be easily adapted to Complementary Metal Oxide Semiconductor (CMOS) technology; therefore, front-end electronics compounds can be realized by using the same technology.…”
Section: Introductionmentioning
confidence: 99%
“…By depositing a metal film on the surface of clothing fabric via magnetron sputtering, the fabric can be given special properties, which expands the application scope of clothing. For example, clothing can be given the properties of electromagnetic shielding, antistatic conduction, intelligent sensing, energy production through thin film solar cells, anti-ultraviolet antibacterial, and infrared shielding functions [13][14][15][16][17]. Jiang et al once prepared copper film deposited nylon yarn by magnetron sputtering at different winding speeds to achieve enhanced electrical conductivity [18].…”
Section: Introductionmentioning
confidence: 99%